2022
DOI: 10.1515/jpm-2022-0196
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ripening as an outpatient procedure in the pandemic – minimizing the inpatient days and lowering the socioeconomic costs

Abstract: Objectives With an increasing incidence of labor induction the socioeconomic costs are increasing and the burden on hospital capacities is rising. In addition, the worldwide SARS-CoV-2 pandemic asks for improvements in patient care during pregnancy and delivery while decreasing the patient-staff contact. Here, we are retrospectively analyzing and comparing a mechanical ripening device that is utilized as an outpatient procedure to misoprostol and dinoprostone as inpatient induction methods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…A retrospective analysis comparing cervical ripening with Dilapan-S in an outpatient procedure with the use of oral misoprostol or vaginal PGE 2 gel in an inpatient setting has shown that cervical ripening with Dilapan-S resulted in a significant reduction of time period from patient admission to the onset of labor, shorter inpatient stay from admission to delivery and fewer hospital days in the outpatient group thus decreasing socioeconomic costs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis comparing cervical ripening with Dilapan-S in an outpatient procedure with the use of oral misoprostol or vaginal PGE 2 gel in an inpatient setting has shown that cervical ripening with Dilapan-S resulted in a significant reduction of time period from patient admission to the onset of labor, shorter inpatient stay from admission to delivery and fewer hospital days in the outpatient group thus decreasing socioeconomic costs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Die ambulante Anwendung osmotischer Dilatatoren war im Vergleich zur stationären Anwendung mit kürzeren stationären Krankenhausaufenthalten und schnellerem Einsetzen aktiver Wehen verbunden, ohne dass es zu signifikanten negativen Vorkommnissen kam 21 . Sie war im Vergleich zur stationären Anwendung von PGE 2 -Vaginalinserts oder Ballonkathetern mit geringeren 22 oder gleichen Kosten und geringerer Arbeitsbelastung 23 verbunden und zeigte in einem retrospektiven Vergleich mit der stationären Anwendung von Misoprostol oder PGE 2 -Vaginalgel ein schnelleres Einsetzen aktiver Wehen und kürzere Krankenhausaufenthalte bis zur Geburt 24 .…”
Section: Diskussionunclassified
“…Ballonkathetern mit geringeren[22] oder gleichen Kosten und geringerer Arbeitsbelastung[23] verbunden und zeigte in einem retrospektiven Vergleich mit der stationären Anwendung von Misoprostol oder PGE 2 -Vaginalgel ein schnelleres Einsetzen aktiver Wehen und kürzere Krankenhausaufenthalte bis zur Geburt[24]. Ballonkatheter, dem 10mg-PGE2 -Vaginalinsert oder der oralen Gabe von Misoprostol.…”
unclassified